Presidential Decree No. 330/2015 Concerning the Establishment of Suez Canal Economic Zone = قرار رئيس جمهورية مصر العربية رقم 330 لسنة 2015 بإنشاء المنطقة الاقتصادية لقناة السويس / presidency - Egypt. presidency (2025)
Presidential of the Republic Decree No. 330 of the year 2015 Concerning the Establishment of Suez Canal Economic Zone قرار رئيس جمهورية مصر العربية رقم 330 لسنة 2015 بإنشاء المنطقة الاقتصادية لقناة السويس